Feminist Epistemology and The Search For Liberating Knowledge - Hidayat, Rachmad (Jurnal Filsafat "WISDOM", 2018)
This paper discusses problems in dealing with masculinized knowledge and scientific enterprises, and seeks alternative epistemological strategies in achieving liberating and un-dominated knowledge production. A general problem with "mainstream" epistemology and philosophy of science from feminist perspectives is that the well accepted concept of knowledge and scientific practices derived from it deny the impacts of social and political dimension toward knowing activities and their results. Feminists observed that men and their masculinities have been reproducing their social and political domination into the practices and standard of objective knowledge. The paper takes on two questions. First, how masculinity as dominant social and political norm has influence the production of knowledge? Second, what epistemological strategies would allow the production of less dominating and liberating knowledge? Feminist theories of knowledge built on the belief that rational inquiry is social practice through which gender as cultural and political norms and reference give deep impacts toward knowing process and it results. A theory of liberating knowledge requires acknowledgement and acceptance of multiple methods and models of knowledge in accordance to specific situation of the knowing subjects. Through such epistemological understanding feminist theorists formulated epistemological strategies to reduce masculinity in the rational inquiries and well accepted science.